TINDAK TUTUR ILOKUSI DALAM FILM MALEFICENT KARYA LINDA WOOLVERTON (SUATU ANALISIS PRAGMATIK) - Karundeng, Patricia; Lasut, Theresia M.C; Lotulung, Donald R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Patricia Karundeng1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Dra. Theresia M. C. Lasut, M.Hum2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Donald Ringgo Lotulung, S.S M.Hum3Â  Â  Â This study entitled â€œIllocutionary Act in the Film Maleficent by Linda Woolverton: A Pragmatic Analysisâ€. The method that is used in this research is descriptive method. The purpose of this study is to identify, classify and analyze the kinds and functions of ilocutionary act in the film Maleficent by Linda Woolverton. The data were collected from conversations between characters, then classified and analyzed by using theory of Searle in Leech (1983). There are five kinds of illocutionary act in the Film Maleficent by Linda Woolverton, those are assertives, directives, commisives, expressives and declaratives. The illocutionary functions of assertives in the film Maleficent by Linda Woolverton are stating, asserting, suggesting, complaining, reporting. The illocutionary function of directives which were used by the characters were asking, commanding and requesting. Advising and ordering functions were not found in film Maleficent. The illocutionary functions of commissives are promising, vowing and offering. The illocutionary functions of expressives are thanking, congratulating, blaming, accusing, praising and apologizing. The illocutionary function of declaratives are punishing and canceling while function like naming, baptizing and promoting were not found in film Maleficent.--------------------------------------------------------Keywords: Illocutionary Act, Kinds and Function, Film Maleficent